KI/TBHP-mediated oxidative cross-coupling of enamines and carboxylic acids under metal-free conditions: a facile access to functionalized 2H-azirines. Issue 13 (30th March 2016) - Duan, Xiyan; Kong, Xianglei; Zhao, Xiaoyong; Yang, Kun; Zhou, Huiyun; Zhou, DongJu; Zhang, Yanping; Liu, Jianwei; Ma, Junying; Liu, Ning; Wang, Zhicheng
Graphical abstract: Abstract: KI/TBHP-mediated oxidative cross coupling of enamines with carboxylic acids has been realized for the synthesis of functionalized 2 H -azirines through the azirination of enamine intermediates. The metal-free strategy has several notable features, including the formation of C–O and C–N bonds in a one-pot procedure, broad functional group tolerance, good reaction yields, short reaction time, and high atom economy. It is the first example for direct formation of functionalized 2 H -azirines via KI/TBHP-mediated intermolecular cross-coupling of enamines and carboxylic acids.